Gani et al Survei Level Kecemasan Peserta Didik Saat Berlatih Renang dan Faktor Penyebabnya - Muhammad Abel; Ruslan Abdul Gani; Rizki Aminudin; Edi Setiawan (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2022)
This study aims to determine the level of anxiety of students in swimming extracurricular. The method used in collecting data to determine the level of anxiety before swimming extracurricular students is a survey method by collecting data using a questionnaire. The subjects in this study were all students who took part in swimming extracurricular at Senior High School 2 Tanjung Pandan, Belitung Regency, totaling 69 people consisting of 41 men and 28 women. The data analysis technique in this study used quantitative descriptive statistical analysis to find the frequency and percentage of anxiety from students. The results of this study indicate that of the 69 students who take swimming extracurricular activities, most of them have high level anxiety in both male and female categories and the triggering factors for anxiety in students are intrinsic and extrinsic factors. So it can be concluded that the anxiety of students in the male and female gender has a level from moderate to high, but it depends on their respective intrinsic and extrinsic factors.